Kemitraan taman bacaan masyarakat dengan lembaga kemasyarakatan dalam diseminasi informasi kesehatan - Tita Nursari; Elnovani Lusiana; Andri Yanto (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. This study aims to explore strategies, stages, and understand the partnership model applied by TBM Sahabat Pena (SP) and Karang Taruna in disseminating health information. Research methods. This study used a qualitative approach with a case study involving interviews, observation, and document study. With a purposive sampling, four informants and one expert were involved from the TBM SP partnership. Data analysis. Data analysis was conducted through data reduction, data presentation, and conclusion. Results and Discussion. The TBM SP creates strategies to establish partnerships among the parties who have a personal interest and collaboration with the TBM manager by using the existing resources. The stages conducted were identified in four stages: initiating, implementating, monitoring & learning, developing and maturing stage. Conclusion and recommendations. All activities related to partnership need to be in line with the TBS vision and mission. The implementation stage is the most influential stage in the success and sustainability of the partnership. The active role of the TBM manager is definitely needed.